Perceptual Salience of Tones, Vowels, and Consonants in Mandarin Speech Errors - Liu, Zifeng; Chitoran, Ioana; Turco, Giuseppina (Language and speech, 2025)
The present study examines the perceptual salience of tonal speech errors compared with segmental errors (consonant and vowel). Tonal errors are observed less often than segmental errors. We thus hypothesize that tone errors are more easily ignored during transcription tasks because tones may have lower perceptual salience relative to segments. We test this hypothesis in Mandarin, via a number reconstruction task. Sixty-nine Mandarin native listeners heard sequences of numbers in which one number was altered by substituting its vowel, consonant, or tone. They were asked to identify which number that was. We found that Mandarin listeners identified the original number most accurately when consonants were substituted. They were the least accurate when vowels were substituted. For tone substitution, the accuracy was lower than for consonant substitution, but not significantly different from vowel substitution. Reaction times to identify a number with tone substitution were comparable to those for other types of substitutions. The results show that, contrary to our hypothesis, tone errors are not perceptually less salient than segmental errors. Specifically, tone errors are as salient as vowel errors and more salient than consonant errors, suggesting a similar phonological status shared by tone, vowel, and consonant in constraining word selection.